Fremde Heimat : Kunst in Baden-Württemberg - Heider, Klaus; Härtling, Peter; Jägersberg, Otto; Lorenz, Ulrike; Marinig, Jagoda; Schlink, Bernhard; Walser, Theresia; Wyss, Beat (Mannheim : Kunsthalle Mannheim, 2010)
Hüppi, Thaddäus ; Oberkofler, Gabriela ; Kreusch, Carolina Camilla ; Sigloch, Daniel ; Schuler, Marco ; Panse, Tino ; Adt, Reinhold ; Braig, Oliver ; Heil, Axel ; Merkel, Klaus ; Sakic, Achim ; Dreher, Peter ; Heider, Klaus ; Winter, Georg ; Filderbahnfreundemöhringen ; Staeck, Klaus ; Brenner, Birgit ; Allenstein, Olga ; Jäger, Ulrika ; Superart.TV ; Weibel, Peter ; Walter, Harry ; Betzwieser, Hagen ; Huttler, Ruth ; Roth, Daniel ; Schulz, Dorothea ; Stattler, Herbert ; Roob, Alexander ; Palmtag, Jürgen ; Rick, Peter ; Hüppi, Alfonso ; Sallas, Joan ; Ackermann, Franz ; Wendel, Pablo ; Schmidt, Werner
Fremde Heimat : Kunst in Baden-Württemberg, Kunsthalle Mannheim, Mannheim, 010-03-28. 2010-06-20
boek
Keywords: Baden-Württemberg; Duitsland